Phosphorylation of the yeast γ-tubulin tub4 regulates microtubule function - Lin, Dennis Tien-chen; Gombos, Linda; Neuner, Annett; Sebastian, Dominik; Olsen, Jesper V.; Hrle, Ajla; Benda, Christian; Schiebel, Elmar (PLOS ONE, 2011)
The yeast γ-tubulin Tub4 is assembled with Spc97 and Spc98 into the small Tub4 complex. The Tub4 complex binds via the receptor proteins Spc72 and Spc110 to the spindle pole body (SPB), the functional equivalent of the mammalian centrosome, where the Tub4 complex organizes cytoplasmic and nuclear microtubules. Little is known about the regulation of the Tub4 complex. Here, we isolated the Tub4 complex with the bound receptors from yeast cells. Analysis of the purified Tub4 complex by mass spectrometry identified more than 50 phosphorylation sites in Spc72, Spc97, Spc98, Spc110 and Tub4. To examine the functional relevance of the phosphorylation sites, phospho-mimicking and non-phosphorylatable mutations in Tub4, Spc97 and Spc98 were analyzed. Three phosphorylation sites in Tub4 were found to be critical for Tub4 stability and microtubule organization. One of the sites is highly conserved in γ-tubulins from yeast to human.